Experimental study of particle size segregation in 2D granular materials under vertical vibrations - Pawarut Jongchansitto (2018)
© The Authors, published by EDP Sciences, 2017. The influence of particle size on segregation phenomena in two-dimensional binary granular mixtures with a similar solid fraction under vertical vibrations is experimentally investigated in this study. Four different particle size ratios (D l /D s ) are varied. The granular mixtures are subjected to vertical vibrations under six different dimensionless accelerations (Γ = 1-6), with constant vibrational amplitude of 5 mm. The vertical segregation coefficient (H) is here introduced to analyse the degree of segregation of the mixtures. We found that the Brazil nut effect, where the larger particle rises to the top, is observed for all the tests whenever the segregation is occurred. The degree of segregation of the mixtures is a function of the coefficient H, which can be divided into 3 zones: a compaction zone with particle mixing (0.0 < H ≤ 0.2), a partially segregated zone (0.2 < H ≤ 0.4), and an apparently segregated zone (0.4 < H ≤ 1.0). The segregation begins when Γ ≥ 2 and then tends to increase when Γ is increased. In addition, the segregation is quite clearly found when D l /D s ≥ 3 and Γ ≥ 3.